New Approaches to Old Questions in Gun Scholarship - Blocher, Joseph (2015)
Reviewing Philip J. Cook and Kristin A. Gross, The Gun Debate: What Everyone Needs to Know; Saul Cornell and Nathan Kozuskanich, The Second Amendment on Trial: Critical Essays on District of Columbia v. Heller; Nicholas Johnson, Negroes and the Gun: The Black Tradition of Arms; Akinyele Omowale Umoja, We Will Shoot Back: Armed Resistance in the Mississippi Freedom Movement; and Craig Whitney, Living with Guns: A Liberal’s Case for the Second Amendment